2018
DOI: 10.4054/demres.2018.39.33
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of death in the United States: The remarkably different mortality patterns between America’s Heartland and Dixieland

Abstract: BACKGROUNDGeographic disparities in mortality have been analyzed by place in myriad ways. Although the people who live in a place continuously change, the health characteristics of those places tend to stay the same; they are persistent. Our work analyzes persistence of mortality across various geographic designations and uncovers the wide-ranging disparities in death across the United States. METHODSUsing 48 years of county-level mortality data, we analyze trends over time and disparities across places using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…These divisional trends were driven by multiple causes of death, including the deaths of despair, cardiometabolic diseases, respiratory disease, and liver cancer. The southern mortality penalty is consistent with recent research showing a persistent and growing mortality penalty for this region (James 2014 ; James and Cossman 2017 ; James et al 2018 ). Together, these findings suggest that the rural southern and Appalachian disadvantage may be generational and impervious to changes in population composition over time.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These divisional trends were driven by multiple causes of death, including the deaths of despair, cardiometabolic diseases, respiratory disease, and liver cancer. The southern mortality penalty is consistent with recent research showing a persistent and growing mortality penalty for this region (James 2014 ; James and Cossman 2017 ; James et al 2018 ). Together, these findings suggest that the rural southern and Appalachian disadvantage may be generational and impervious to changes in population composition over time.…”
Section: Discussionsupporting
confidence: 89%
“…James and Cossman ( 2017 ) similarly found that both white and black mortality rates were comparatively higher in medium-sized nonmetro counties and lower in the smallest nonmetro counties. James et al ( 2018 ) combined RUCCs and the nine Census divisions, finding that persistently high mortality was most heavily concentrated in rural counties in the East South Central division. Murray et al ( 2006 ) divided the U.S. into eight Americas based on race, region, and population density, finding comparatively high life expectancy (LE) in the Great Plains and low LE in the Deep South.…”
Section: What We Know About Within-rural Differences In Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our data do not have the detail to directly address concerns about urban-rural mortality gaps (Cossman et al 2010;James 2014). Future research could apply innovative data linkages to formally model variation in urban-rural early life mortality gaps across state contexts, extending prior descriptive research (James, Cossman, and Wolf 2018). Extant research on geographic variation in adult mortality has been increasingly moving in this direction, linking large-scale highquality survey data to diverse administrative and historical data sets to better understand how macro-level contexts and changes influence region and even statespecific health outcomes (Hayward et al 2018;Montez, Hayward, and Wolf 2017;, including mortality .…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent work, Singh and colleagues (2013) find that much of this southern disadvantage is driven by sustained socioeconomic deprivation at the county level, which, combined with higher risks of death in both urban and rural settings, contributes to higher levels of mortality from homicide, suicide, unintentional injuries (primarily from motor vehicle accident deaths), and HIV/AIDS. Moreover, southern rural settings have been associated with some of the highest age-specific mortality rates in the country, contributing to a wider urban-rural mortality gap (Cossman et al 2010;James, Cossman, and Wolf 2018), which some studies suggest may be impacted by statelevel factors such as expenditures on public health (Cossman, James, and Wolf 2017; James 2014).…”
Section: The Southern Disadvantage In Us Mortalitymentioning
confidence: 99%